The Establishment of Sociability in A Student Housing: Architectural and Psychological Aspects - Muhammad Ismail Hasan; Ika Zenita Ratnaningsih (Green Publisher, 2025)
Sociability is a fundamental element of Indonesian culture that emphasizes mutual acceptance and respectful presence in shared social spaces. This study explores how sociability is established and experienced by male students living in shared student housing, with a particular focus on both architectural and psychological dimensions. Employing a qualitative grounded theory approach, data were collected through a Focus Group Discussion (FGD) with 30 male residents occupying multi-user bedrooms. Participants described their everyday interactions and spatial experiences within the housing environment. The findings reveal that sociability is cultivated through shared routines, local socio-cultural practices, and communal norms, which foster interpersonal closeness among residents. Importantly, the spatial layout, such as openness, proximity, and availability of communal areas, plays a critical role in enabling social encounters. From a psychological perspective, students’ perceived person–environment fit emerged as a key factor influencing their comfort, engagement, and sense of belonging. This research contributes to the understanding of sociability in student housing by integrating architectural and psychological insights. It also underscores the importance of designing student living environments that promote cultural congruence, social connectivity, and psychological well-being, especially within Indonesian collectivist societies.